The Advantage of the Drug Nifedipine in the Treatment of Arterial Hypertension (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Arterial hypertension is an increase in blood pressure. Older, obese people often suffer from this disease. Arterial hypertension is primary and secondary. Primary hypertension This is a type of hypertension that is not related to other systems and is not caused by secondary factors. There are no specific causes, but there are risk factors that can cause it (breeding, age, ace, hypodynamia, obesity, high consumption of NaCl, alcoholism, smoking, hyperlipidemia, stress). Secondary hypertension. This is a type of hypertension associated with other systems and drugs. These are: kidney, heart, lung, endocrine system, nervous system, and there are types found in pregnant women.